Undergraduates' Perceptions of how Post-secondary Education Characteristics Shaped their Transition to University - Shields, Sam (International Journal of Educational and Life Transitions, 2023)
It is well known that privately educated young people benefit from access to competitive degree programmes at the most prestigious universities. Less is known about how stratified post-secondary education provision and socio-economic differences impact upon state educated young peoples’ transitions into higher education. Using interview data from twelve undergraduates reflecting on their journeys into higher education, differences in post-secondary education experiences were explored. The findings indicated that middle-class university entrants who had studied at selective sixth-forms and sixth-form colleges were exposed to a range of cultural practices to maximise a successful and smooth entry into higher education. Conversely, the working-class participants studying at small school sixth-forms and further education colleges were more likely to encounter structural factors which resulted in complex and difficult transitions into higher education. However, for working-class students who had received individualised and tailored support from their teachers, they experienced similarly smooth transitions as middle-class entrants, highlighting the impact teachers can have in supporting working-class university applicants. These findings indicated that whilst universities are doing much to widen participation, this cannot be done in isolation of consideration of post-secondary education characteristics which may (or may not) facilitate smooth transitions for all young people wishing to access higher education.
Keywords: Transition; widening participation; post-secondary education; cultural practices; ethical teacher habitus